1985
DOI: 10.1088/0022-3727/18/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Electron swarm parameters in oxygen and methane

Abstract: Experimental measurements of the drift velocity and the ratio of longitudinal diffusion coefficient to mobility for electrons have been obtained for the range of 25<or=E/N<or=848 Td for oxygen and 0.28<or=E/N<or=848 Td for methane (1 Td=10-17 V cm2). The results obtained from a Monte Carlo simulation have been compared with the present and previously obtained data and a good fit has been achieved for the entire range of E/N. As a result of this investigation, two sets of cross sections are given wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
4
14
0
Order By: Relevance
“…The calculated diffusion coefficients (drift velocity and transversal diffusion over the mobility ratio) agree with swarm experiments [29,[55][56][57][58][59][60] within 10% in the whole 0.01-10 Td range of reduced-electric field, see Figure 4. However, it was shown already in the past that in the case of methane Boltzmann's multi-term [61,62] or Monte Carlo [63] methods are needed.…”
Section: Integral Cross Sectionssupporting
confidence: 79%
See 1 more Smart Citation
“…The calculated diffusion coefficients (drift velocity and transversal diffusion over the mobility ratio) agree with swarm experiments [29,[55][56][57][58][59][60] within 10% in the whole 0.01-10 Td range of reduced-electric field, see Figure 4. However, it was shown already in the past that in the case of methane Boltzmann's multi-term [61,62] or Monte Carlo [63] methods are needed.…”
Section: Integral Cross Sectionssupporting
confidence: 79%
“…Experimental swarm parameters: (a) the drift velocity and (b) the transverse diffusion coefficient, compared to solutions of two-term Boltzmann equation [38] using MERT-derived momentum transfer cross-section as the input data. The experimental results are from Schmidt [29], Hunter et al [55], Haddad [56], Al-Amin et al [57], Cochran and Forester [58], Millican and Walker [59] and Pollock [60]. To choose recommended vibrational integral CS we performed a thorough screening of theories [15,45,51,52], beam experiments [30,31] and swarm analysis [29,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Since the drift velocity as well as the diffusion coefficient are determined from a set of measurements using different drift lengths, field uncertainties and boundary effects near the anode cancel out as does the time resolution of the detector and the initial spread of the electron 'cloud'. The probability that an electron starting at a distance z passes the totally absorbing boundary between the drift region and the proportional counter in the time interval Ct, Hdt) is given by (Chandrasekhar 1943) ( z…”
Section: Apparatus and Experimental Procedures (2a) Principle Of The Mmentioning
confidence: 99%
“…3 for comparison. The experimental studies in methane have been reported by investigators such as Al-Amin et al, 21 Haddad, 23 FIG. 2.…”
Section: Resultsmentioning
confidence: 89%
“…In Fig. 3, the drift velocities taken from AlAmin et al 21 and Hunter et al 22 are denoted by W because it is unclear whether their velocities are equivalent to W r or W m . As is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%